Anti-M Alloimmunization following Term Stillbirth: A Case Report and Review of the Literature - Beck, Manisha M.; V., Hamsavardhini; Navaneethan, Preethi; Kumar, Manish (Journal of Fetal Medicine, 2023)
Alloimmunization due to anti-M antibodies are rare since they present as naturally occurring immunoglobulin M antibodies, which do not cross the placenta. Very rarely, these may convert to immunoglobulin G antibodies and cause hemolytic disease of the fetus and newborn. We present the case of a fifth gravida, with previous two miscarriages and an unexplained stillbirth, booked with us for the 8 weeks. At booking, she was found to have anti-M antibodies with titers of 1:2, which was stable throughout pregnancy. At 35 weeks, there was evidence of severe fetal anemia and features of hydrops on the ultrasound scan, requiring delivery. Neonatal direct Coombs test was positive. Baby had a hemoglobin of 8.8 mg/dL and a reticulocyte count of 5.5% at birth, requiring two units of blood transfusion. He also required 6 days of intensive phototherapy. Alloimmunization due to anti-M antibodies should be suspected in women with previous bad obstetric history. The maternal antibody titers may not be a true reflection of the severity of fetal affection, and hence not reliable for monitoring in pregnancy
Keywords: alloimmunization; anti-M antibodies; fetal hydrops; hemolytic disease of fetus and newborn; stillbirth